Influence of sulfur fumigation on glycoside profile in Platycodonis Radix (Jiegeng). Issue 1 (December 2016) - Ma, Xiao-Qing; Li, Su-Mei; Chan, Chi; Su, Tao; Li, Wei-Dong; Cao, Hui; Fong, Wang-Fun; Yu, Zhi-Ling
Abstract Background Over recent decades, sulfur fumigation is becoming abused in processing some freshly harvested herbs used as both medicine and food, although it has been questioned whether sulfur fumigation will change the efficacy and safety of the herbs. One of the herbs commonly processed by sulfur fumigation is Platycodonis Radix (Jiegeng in Chinese). Glycosides are the main bioactive components ofJiegeng . Up to the present, no study has been carried out to evaluate the impact of sulfur fumigation on glycoside profile ofJiegeng . Methods A rapid and versatile ultra-high performance liquid chromatography coupled with ultra-high resolution quadrupole time-of-flight mass spectrometry (UHPLC UHD Q-TOF MS/MS) method was developed for comprehensive analysis of the glycoside profiles of sulfur-fumigated and air-driedJiegeng samples. Results Twenty-three glycosides were detected in air-dried and sulfur-fumigatedJiegeng samples. After sulfur fumigation, the peak heights of eight glycosides, namely platycogenin A, platycodin D, platycodin D2, platycodin D3, polygalacin D, polygalacin D2, deapio-platycodin D and 3″-O -acetylplatycodin D2, remarkably decreased; while peak heights of five glycosides, namely syringin, lobetyolin, platycoside E, deapio-platycodin D2 and deapio-platycoside E, slightly increased; in addition, peaks of ten glycosides, platycodin A, platycodin C, platycodin V, platycoside C, 16-oxoplatycodin D, 2″-O -acetylpolygalacin D, 2″-O -acetylpolygalacin D2, 3″-O -acetylpolygalacin D, 3″-O -acetylpolygalacin D2, and platycogenic acid B, disappeared. Conclusion Sulfur fumigation caused significant changes of glycoside components ofJiegeng . Further investigations are warranted to explore how these chemical changes occurred and whether these changes would affect the efficacy and safety ofJiegeng .